Identifying financial constraints - Laurens Cherchye; Bram De Rock; Annalisa Ferrando; Klaas Mulier; Marijn Verschelde (European Central Bank (ECB), 2020)
We propose a new methodology to recover firm-time varying financial constraints from firms' production behavior. We model financial constraints as the profitability that firms forgo when budget constraints on production inputs bind, impeding them from using the optimal level of inputs and technology. We estimate and validate our measure using unique data combining firms' balance sheets with survey information on self-reported financial constraints, like loan rejections. In contrast to three popular indices of financial constraints, our measure recovers financial constraints beyond observable firm characteristics, recovers cross-sectional and time-varying stylized facts of financial constraints, and is applicable to both public and private firms.
Keywords: E44; G00; G30; G32; 330; Financial constraints; identification; access to finance; indicators; production function